2020
DOI: 10.21203/rs.3.rs-22059/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sports activity participation after curved periacetabular osteotomy for acetabular dysplasia

Abstract: Background: Curved periacetabular osteotomy (CPO) was developed to treat acetabular dysplasia. Given that CPO can improve physical function in the early post-operative period, patients might be able to participate in sports activities post-operatively. Therefore, this study examined the post-operative sports activity participation and characteristics of acetabular dysplasia patients who have undergone CPO.Methods: A total of 52 patients who underwent CPO for acetabular dysplasia were given a questionnaire on p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a case-control study, Hara et al 36 investigated sports participation in patients with BD before and after PAO and found that the number of patients who participated in sports significantly increased from 31.1% preoperatively to 55.3% postoperatively. Similarly, Takahashi et al 68 examined postoperative sports activity participation in 43 patients with dysplasia who underwent curved PAO and found that 72% of patients participated in sports activity postoperatively, although most sports were low impact. Additional comparative studies are warranted to better define the role of PAO in athletes with BD.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study, Hara et al 36 investigated sports participation in patients with BD before and after PAO and found that the number of patients who participated in sports significantly increased from 31.1% preoperatively to 55.3% postoperatively. Similarly, Takahashi et al 68 examined postoperative sports activity participation in 43 patients with dysplasia who underwent curved PAO and found that 72% of patients participated in sports activity postoperatively, although most sports were low impact. Additional comparative studies are warranted to better define the role of PAO in athletes with BD.…”
Section: Discussionmentioning
confidence: 99%
“…Residual hip joint dysplasia is a sequela of incorrect development of the hip joint acetabulum during fetal development or a result of incorrect treatment during infancy. It is estimated that in among young patients, up to 80-90% of cases of hip joint osteoarthritis develop as a result of hip joint dysplasia [1,2,3].…”
Section: Introductionmentioning
confidence: 99%